POTENSI EKSTRAK METABOLIT SEKUNDER Eugenia uniflora L. SEBAGAI BAHAN PENGAWET TAHU - Genesis Tria; Nurhamidah Nurhamidah; Hermansyah Amir (ALOTROP, 2018)
[POTENTIAL OF Eugenia uniflora L SECONDARY METABOLITES EXTRACT AS A TOFU PRESERVATIVE]. The purpose of this research is to know the secondary metabolite compounds from the Eugenia uniflora L (Dewandaru) fruit extracts , as well as to measure the potential of water extract from the fruit of E. uniflora L for the use in the tofu preserve as well as measure the impact of the addition of water extract of the fruit of E. uniflora L against moisture, pH, protein on tofu. The process of preserving test against tofu on the research done by soaking time at 2, 3 and 4 hour with each variation of the concentration of extract at  10, 15 and 20% as well as the observation time at 24 and 48 hours for each treatment.The result of the test water extract of the fruit of the phytochemical profile E. uniflora L showed the content of alkaloids, flavonoids, phenolic , saponins and steroid compounds. Test results from the granting of water extract from the fruit of E.uniflora L in the preserve of tofu with the variation of concentration and soaking time is proven to affect the value of water content, pH, and protein on tofu that was tested.The results of the research done indicate that the granting of a water extract of the fruit of E.uniflora L proven useful to be used as a natural preservative for tofu at 24 hours with a 20% concentration and a soaking time at 2 and 3 hours. From the results, it can be concluded that water extracts from the fruit of E.uniflora L. potential to be used as a natural preservative for tofu.